Responsabilidad social empresarial y mercado de trabajo - Garavito, Cecilia (2008)
The objective of this article is to analyze the reason why Corporate Social Responsibility (CSR) policies in Peru focus on issues related to the community and the environment, neglecting labor issues. CSR labor programs are those who aim to offer a «productive and decent work, under conditions of freedom, equality, safety and human dignity». After an exhaustive review of the theoretical literature and the analysis of CSR policies in Peru, we believe that the reason for the low interest on CSR labor policies is the lack of demand from society for such policies. We state the existence of a social necessities hierarchy where, due to the poverty level and the weakness of our institutional system, labor rights are considered a luxury good. In this context, the interest on poverty and environmental issues, even if it has an internal component, is also associated to the demand from developed countries and multinational firms. We can say the same thing about today’s debate about labor rights and free trade agreements.